Identifying the Antecedents and Consequences of Health Leadership in the Hospitals of Lorestan University of Medical Sciences, Health and Medical Services - Beiranvand, Farideh; Vedadi, Ahmad; Amir Kabiri, Alireza; Boroumand , Zahra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this article was to investigate the antecedents and consequences of the conceptualized model of health leadership for the promotion of employee health in the hospitals of Lorestan University of Medical Sciences, Health and Medical Services.Methods: The research method employed was qualitative, using thematic analysis, and was applied in nature. The participants in the study included some experts in the field of management in the health sector, who were selected based on purposive sampling. Fourteen individuals were chosen based on specific criteria (management service history in the health sector, willingness to be interviewed, general management experiences, publications in the health and management fields). The sample size was also determined based on the principle of theoretical saturation. The research tool was semi-structured interviews, which were developed through several rounds of feedback with experts. Its validity was confirmed through expert opinions, and reliability was assessed through inter-coder agreement coefficient. Data were analyzed using coding method.Findings: The results indicated that for identifying the antecedents and consequences of health leadership in the hospitals of Lorestan University of Medical Sciences, there are four overarching themes (health leadership, health leadership mechanisms, antecedents of health leadership, and consequences of health leadership) and 22 organizing themes.Conclusion: The findings of the research provide an opportunity to respond to well-being and as a part of identifying significant prominent themes in human capital, particularly aiding and supporting management in reducing turnover and relocation for the health of employees.